Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5334/jcr.212
|View full text |Cite
|
Sign up to set email alerts
|

Daily and Estral Regulation of RFRP-3 Neurons in the Female Mice

Abstract: Female reproductive success relies on proper integration of circadian-and ovarian-signals to the hypothalamic-pituitary-gonadal axis in order to synchronize the preovulatory LH surge at the end of the ovarian follicular stage with the onset of the main active period. In this study, we used a combination of neuroanatomical and electrophysiological approaches to assess whether the hypothalamic neurons expressing Arg-Phe amiderelated peptide (RFRP-3), a gonadotropin inhibitory peptide, exhibit daily and estrous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This loss of daily variation in the peptidergic input on RFRP-3 neurons may be partly responsible for the observed loss of the daily regulation of RFRP-3 neuronal activity. Indeed, both peptides may be involved in the daily regulation of RFRP-3 neurons, since previous studies have reported that VIP inhibits (Russo et al, 2015) and AVP activates (Angelopoulou et al, 2021) RFRP-3 neurons at specific time points.…”
Section: Discussionmentioning
confidence: 99%
“…This loss of daily variation in the peptidergic input on RFRP-3 neurons may be partly responsible for the observed loss of the daily regulation of RFRP-3 neuronal activity. Indeed, both peptides may be involved in the daily regulation of RFRP-3 neurons, since previous studies have reported that VIP inhibits (Russo et al, 2015) and AVP activates (Angelopoulou et al, 2021) RFRP-3 neurons at specific time points.…”
Section: Discussionmentioning
confidence: 99%
“…Sex steroid hormones, likewise, negatively or positively feedback onto neurons in the hypothalamus to control LH and FSH release (for review see Wang and Moenter, 2020 ). Positive feedback is mediated by kisspeptin neurons in the rostral hypothalamus, whereas negative feedback is modulated by both kisspeptin neurons in the caudal hypothalamus and gonadotropin-inhibitory neurons ( Angelopoulou et al, 2021 ; Chassard et al, 2015 ; Gibson et al, 2008 ; Smith et al, 2005 ; Williams et al, 2011 ). Interestingly, both of these feedback loops, positive and negative, receive input from the SCN ( Vida et al, 2010 ), suggesting the clock is involved in regulating sex hormone concentrations.…”
Section: Defining Sex Hormones and Their Mode Of Action In The Scnmentioning
confidence: 99%